Alisher Navoi's Role in Historical and Literary Works Similarities and Differences (Texas Journal of Multidisciplinary Studies, 2022)
This article examines the role of Alisher Navoi in the works of literature, the interpretation and study of the life and work of the artist. The research is used works of art that provide information about the artist based on historical facts, as well as works of art that are close to historical truth. The relationship between Hussein Boykaro and Alisher Navoi, described in many works, emphasizes the description of Navoi's life in Samarkand. The views of the artists who created the work about Navoi in this regard are compared.